1979
DOI: 10.1021/bk-1979-0100.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pass Leaching of Nuclear Melt Glass by Groundwater

Abstract: The work presented in this report was supported by the Department of Energy (DOE) through the Nevada Operations Office (NVOO) as part of the Radionuclide Migration Program at the Nevada Test Site (NTS). The purpose of this program is to inves tigate the potential for underground migration of radionuclides in groundwater from the sites of underground nuclear explosions. Borg et al. have comprehensively reviewed this subject and have included an annotated bibliography (1). Levy (2) discusses in detail the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…matrix dissolution (most of the Na data greater than 10 −3 are for times earlier than 5 days). Therefore our predicted value of 10 −3.3 is in fair agreement with long-term glass dissolution rates based on Coles et al (1978). Failor et al (1983) did further flow-through tests on the Cambric glass under similar conditions, but included longer test durations.…”
Section: Comparison With Experimental Datasupporting
confidence: 78%
See 3 more Smart Citations
“…matrix dissolution (most of the Na data greater than 10 −3 are for times earlier than 5 days). Therefore our predicted value of 10 −3.3 is in fair agreement with long-term glass dissolution rates based on Coles et al (1978). Failor et al (1983) did further flow-through tests on the Cambric glass under similar conditions, but included longer test durations.…”
Section: Comparison With Experimental Datasupporting
confidence: 78%
“…There are two reports which provide the rate of release of elements from the Cambric melt glass in flow-through dissolution tests. Coles et al (1978) report release rate data at 25…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…An earlier study by Essington and Sharp (1968) studied the 2 day and 56 day equilibration of debris from the 1957 RAINIER with synthetic sodium bicarbonate groundwater to investigate the nature of radionuclide release and dependence of particle size. Coles et al (1978) reported initial 120 day results of a single pass leaching of a single nuclear explosive melt glass using bicarbonate groundwater from well 5B at the Nevada Test Site; Failor et al (1983) reports on the final results of the same experiment for a 420 day leaching trial for three melt glasses. Batch leaching experiments of nuclear explosive melt debris using bicarbonate water from NTS well J-13 and deionized water has been reported by Thompson (1990Thompson ( ,1991Thompson ( , and 1994.…”
Section: Introductionmentioning
confidence: 99%